Developing flash flipbook as a learning resource to improve students’ digital literacy in elementary school - Alviyana Jami’atus Syifah; S. Suratmi; H. Hartono (Universitas Muhammadiyah Malang, 2025)
Learning resources in primary schools have not fully utilized digital technology. Effective learning resources can increase students' knowledge and learning activities. This research aims to produce learning resources in the form of flash flipbooks that are valid, practical, and effective for improving digital literacy of elementary school students. The research method used is Research and Development (R&D) by applying the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects of this study were fourth grade students in the 2023/2024 school year as many as 27 students. Data were collected through interviews, product validation questionnaires, student response questionnaires, and digital literacy tests. The results showed that flash flipbooks are very valid for use in learning in elementary schools after going through a validation process by media experts, material experts, and practitioners. One to one and small group trials show that flash flipbooks are very practical to use. In addition, the results of the field trial showed an increase in digital literacy with a moderate category. Overall, flash flipbook products can be used in learning with a very feasible, practical category, and can improve digital literacy of elementary school students.